Preparation and Electrochemical Performance of a Graphene Cathode Catalyst Decorated With Pt by Prolysis - Wang, Xi; Ren, Ying; Suo, Ni; Zhang, Guifeng (Frontiers in Energy Research, 2022)
For fuel cells, to produce high-quality and low-platinum catalyst is a pressing technical problem. In this study, graphene cathode catalysts with controllable platinum content were decorated by pyrolyzing chloroplatinic acid under various process parameters to obtain a high catalytic activity and durability. The results show that platinum particles generated by pyrolyzing chloroplatinic acid are uniformly loaded on graphene without agglomeration. The average particle size of platinum particles is about 2.12 nm. The oxygen reduction reaction catalytic activity of catalyst samples first increases, then decreases with increasing platinum loading in cyclic voltammetry and LSV. Compared with the commercial Pt/C (20 wt% Pt) catalyst, the initial potential and the current density retention rate of the catalyst decorated with 8% platinum are 55 mV and 23.7% higher, respectively. From i-t curves, it was found that the stability of the catalyst prepared in this paper was improved compared with the commercial Pt/C catalyst. The catalysts prepared in the present research exhibits superior catalytic activity and stability.